Seasonal and spatial variation of the Montagu's Harrier's Circus pygargus diet in Eastern Poland. Issue 2 (2nd April 2016) - Mirski, Paweł; Krupiński, Dominik; Szulak, Krzysztof; Żmihorski, Michał
Abstract : Capsule: The diet of the Montagu's Harrier Circus pygargus is variable and comprises the most available prey at a given time of the season. We found no evidence for a relationship between diet and land-use in the core foraging zone. Aims: We investigated whether the diet of the Montagu's Harrier reflects the available prey and how it changes across the breeding season and in relation to land-use. Methods: We analysed pellets collected at nests between 2007 and 2011. We looked for nonlinear patterns in the occurrence of prey categories in the pellets as a nonlinear function of the Julian date. Moreover, we tested whether the diet is affected by land-use within a radius of 2299 m from the nest. Results: Four thousand four hundred and sixty-five prey items were found in 880 pellets and 76 prey remains collected at 63 sites. The diet did not depend on the land-use structure but showed a significant temporal variation. Conclusions: The diet of the Montagu's Harrier follows the availability of the prey in the foraging habitat. We conclude that the type of land-use in the vicinity of the nesting habitat has a rather weak effect on the diet of the Montagu's Harrier.